2010
DOI: 10.3166/rfg.202.145-161
|View full text |Cite
|
Sign up to set email alerts
|

Réseaux de conseils d’administration et adoption de pratiques de gouvernance d’entreprise

Abstract: Les développements récents des perspectives cognitives de la gouvernance d'entreprise considèrent le conseil d'administration comme un lieu d'apprentissage et un apporteur de ressources cognitives (Charreaux et Wirtz, 2006). Cette recherche 1 repose sur l'idée que les réseaux de conseils d'administration (CA) constituent un mode d'acquisition de connaissances et de compétences. L'objectif est de comprendre le rôle de ces réseaux dans l'adoption des pratiques de gouvernance d'entreprise. Plus particulièrement, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…Henceforth, the board is a place for learning and a provider of cognitive resources (Charreaux and Wirtz, 2007). Del Vecchio (2010) confirms in the French context that board interlocks are a way of acquiring knowledge and skills. She adds that the density 555 Board interlocks and corporate social responsibility of relations and their concentration around a node are key parameters to improve network efficiency.…”
Section: Bod's Involvement In Csrmentioning
confidence: 75%
See 1 more Smart Citation
“…Henceforth, the board is a place for learning and a provider of cognitive resources (Charreaux and Wirtz, 2007). Del Vecchio (2010) confirms in the French context that board interlocks are a way of acquiring knowledge and skills. She adds that the density 555 Board interlocks and corporate social responsibility of relations and their concentration around a node are key parameters to improve network efficiency.…”
Section: Bod's Involvement In Csrmentioning
confidence: 75%
“…Board interlocks and the adoption of CSR practices. Board interlocks are a privileged channel for knowledge transfer in CSR and could play an important role in the adoption of governance practices (Del Vecchio, 2010). Thus, according to Davis and Greve (1997), changes in governance practices within the board of directors may be due to a process of adaptation to practices observed in other boards on which the directors sit.…”
Section: Bod's Involvement In Csrmentioning
confidence: 99%
“…Directors with multiple board seats benefit from broader social networks, which makes these actors valuable resources (De Villiers et al, 2011). Del Vecchio (2010) confirmed that board interlocks are a way for directors to acquire knowledge and skills.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 98%
“…In addition, social capital theory posits that individuals possess various levels of social capital that they have inherited or acquired, according to their social class, which allows them to access different types of resources and privileges such as recognition, reputation, fame, economic capital, and financial capital (Bourdieu, 2000). Organizations seek after candidates with social networks because they enable economic growth through their connections (Ameer et al , 2010; DelVecchio, 2010) by facilitating access to key resources. Governance practices are thus mechanisms that increase social connections within companies, but always with the aim of creating value, either for individuals or for organizations, or both.…”
Section: Theoretical Foundationsmentioning
confidence: 99%